Efektivitas Sistem Fifo dalam Meningkatkan Efisiensi Operasional dan Kualitas Produk di PT. ABC - Mukti, Anggoro Daru; Saripudin, Ahmad (Jurnal sosial dan sains, 2025)
The automotive industry is one of the key industries in Indonesia's economy. This industry continues to grow rapidly due to the increasing demand for private vehicles. This encourages automotive companies to enhance efficiency and effectiveness in their production processes. This study aims to describe the application of the FIFO (First In, First Out) method in inventory control. The research employs a case study method with a qualitative approach. The findings indicate that the use of color labels and systematic record-keeping has helped ensure product quality and prevent damage to goods. In-depth analysis of fluctuations in the volume of incoming and outgoing goods should also be considered by PT. ABC to predict future warehouse capacity needs.